Association between osteosarcopenia and cognitive frailty in older outpatients visiting a frailty clinic. (January 2022) - Inoue, Tatsuro; Shimizu, Akio; Satake, Shosuke; Matsui, Yasumoto; Ueshima, Junko; Murotani, Kenta; Arai, Hidenori; Maeda, Keisuke
Highlights: Osteosarcopenia was independently associated with cognitive frailty. Osteosarcopenia had a higher odds ratio than each alone in association with cognitive frailty. Decreased executive functions and orientation were associated with osteosarcopenia. Abstract: Purpose: Osteosarcopenia and cognitive frailty are both risk factors for falls and fractures. The purpose of this study was to determine the association between osteosarcopenia and cognitive frailty. Materials and Methods: This was a cross-sectional secondary data analysis of the Frailty Registry Study with outpatients aged ≥65 years who visited a frailty clinic at a geriatric hospital. Osteoporosis was defined as a bone mineral density < 70% of the young adult mean. Sarcopenia was diagnosed according to the Asian Working Group for Sarcopenia 2019 criteria. Cognitive frailty was defined as the coexistence of physical frailty and mild cognitive impairment. Physical frailty was evaluated according to Japanese Cardiovascular Health Study criteria, whereas mild cognitive impairment was defined as a Mini-Mental State Examination score ≥ 24 points and a score ≤ 25 points on the Japanese version of the Montreal Cognitive Assessment. We performed multivariable logistic regression analysis to investigate the association between osteosarcopenia and cognitive frailty. Results: The data of 432 patients were analysed. The prevalence of osteosarcopenia and cognitive frailty was 10.2% and 20.8%, respectively. Logistic regression analysis revealed that osteosarcopenia was independently associated with cognitive frailty with a higher odds ratio than osteoporosis or sarcopenia alone. Lost points in visuospatial abilities/executive functions and orientation were significantly associated with osteosarcopenia. Conclusions: Combination of osteoporosis and sarcopenia is more likely to be associated with physical and cognitive decline than osteoporosis and sarcopenia alone. The mechanism by which osteosarcopenia is associated with decreased visuospatial abilities/executive functions and orientation needs to be addressed.